Implementasi Pendidikan Moderasi Beragama Berbasis Budaya Lokal di Pondok Pesantren Pangleburan Banjarnegara - Solechan, Solechan; Sintasari, Beny (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This research discusses the implementation of religious moderation education based on local culture at the Pangleburan Islamic Boarding School, Banjarnegara. The aim of this research is to analyze Religious Moderation Education Based on Local Culture at the Pangleburan Islamic Boarding School, Banjarnegara and its impact on the character of the students. The research method used is qualitative with a case study approach, which involves field observations, in-depth interviews with Islamic boarding school caregivers, teachers and students, and analysis of related documents. The results of the research show that religious moderation education at the Pangleburan Islamic Boarding School has succeeded in integrating Islamic values with local traditions in its curriculum through integrative methods and contextual learning. Religious moderation education is also carried out through strengthening the value of tolerance in the form of the Ngopi Sareng assembly and preserving cultural traditions such as Selametan, Nyadran Gede and Suran. This approach is effective in forming the character of students who not only understand Islamic teachings textually, but also respect the diversity of cultures and traditions in the surrounding community.